Tristan Strong destroys the world - Mbalia, Kwame (Mbalia, Kwame. Tristan Strong, 2020)
Seventh-grader Tristan Strong is barely recovered from his last adventure in the land of Alke when a vengeful creature called the Shamble Man abducts his grandmother Nana from the family farm in Alabama. Tristan must head back to Alke, and get help from African gods and black folktale heroes to save her--because his powers seem to have disappeared with Nana.